Effect of Antioxidants and Dehanding Methods under Different Temperature Levels on the Control of Banana Crown Browning - S. Ismaili, Elawam S. Ismaili; E. Elkashif, Mohamed; M. Elamin, Osman (المجلة الزراعية, 2021)
Two experiments were conducted at the National Institute for the Promotion of Horticultural Exports, University of Gezira, Sudan, during the period from 2000 to 2001 to investigate the effects of dehanding methods and antioxidants under two temperature levels on the control of banana crown browning. Dehanding methods included separation of hands under water or in air and cutting the hands using a knife under water or in air. The antioxidants were thiourea (1%), aluminum potassium sulfate (1%), ascorbic acid (150 ppm) and wax dissolved in petroleum ether. Dehanding by separation significantly reduced crown browning as compared to the other methods. The best antioxidants in reducing crown browning were thiourea and potassium aluminum sulfate which are sulfur-containing compounds and had an antioxidant activity. Banana hands stored at 14C˚ had significantly less crown browning as compared to those kept at 35C 0 because the lower temperature reduced the activity of polyphenoloxidase enzyme which is responsible for banana crown browning. The interaction effects between antioxidants and temperature showed that the antioxidants followed the same trend mentioned previously within each temperature level, but were more effective in reducing banana crown browning at 14 0 C.